EMBRYONIC AND LARVAL DEVELOPMENTS OF SCHIZOTHORAX CURVIFRONS MECKEL AS OBSERVED IN THE LABORATORY - Gupta, S S; Subla, B A (Indian Journal of Fisheries, 2011)
Fertilized eggs of Schizothorax cnrvifrons obtained by dry-stripping method were reared for studying the early stages in the life history of the species. Rate of fertilization ranged between 79.61 and 84.43%. The larvae released from the egg shells rested at the bottom, nourished by the bulbous sac, exhibiting no feeding movements. After 10-12 days, the yolk-sacs having disappeared, the larvae started to feed. All the important body organs were formed and become functional after 30 days of hatching, and at the 45th day after hatching the fry almost took the shape of the adult, attaining a size of 18-20 mm